Analysis of Environmental Impact on Fertilizer Industry Using Life Cycle Assessment (LCA) Method - Maulana Akbar Abdilah; Atikha Sidhi Cahyana (Universitas Muhammadiyah Sidoarjo, 2022)
Based on observations made at PT. Petrokopindo Cipta Selaras, the company releases a number of substances during the organic fertilizer production process. The method used to analyze the environmental impact produced by PT. Petrokopindo Cipta Selaras is a Life Cycle Assessment (LCA) method. This method was chosen because by using this method a mechanism can be carried out to analyze and take into account the total environmental impact of a product in a production process. This research was conducted to determine the magnitude of the resulting environmental impact and then determine alternative improvements using the Analytic Hierarchy Process (AHP) method. It is known that the distribution process is the process that produces the largest environmental impact with the magnitude of 173200616 tons of CO2 and 14672.67214 tons of SO2. And the alternative improvement in the selected distribution process is to replace the trucks with a capacity of 8 tons to 50 tons to reduce the impact on the environment in the distribution process.